2013
DOI: 10.1179/1607845413y.0000000093
|View full text |Cite
|
Sign up to set email alerts
|

Over expression of HIF-1α in human mesenchymal stem cells increases their supportive functions for hematopoietic stem cells in an experimental co-culture model

Abstract: Full-length cDNA of human HIF-1α was inserted into human bone marrow mesenchymal stem cells by pcDNA.3.1 non-viral plasmid vector, and the effect of this over expression on production of some hematopoietic growth factors was explored. Moreover, using a co-culture system, the interactive impact of HIF-1α-overexpressed mesenchymal stem cells on hematopoietic stem cells was evaluated. Results Over expression of HIF-1α in mesenchymal stem cells in normoxia increased production of one of the most important hematopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Genetic manipulation promotes the viability of stem cell engraftment by overexpression of cytoprotective genes. The common overexpressed genes in promoting the survival of mesenchymal stem cells (MSCs) include v-Akt Murine Thymoma Viral Oncogene (AKT) [10], B-cell lymphoma 2 (Bcl-2) [11], heat shock protein 20 (Hsp20) [12], nuclear factor related (erythroid-derived 2)-like 2 (Nrf2) [13], heme oxygenase-1 (HO) [14,15], endothelial nitric oxide synthase (eNOS) [16], connexin 43 (Cx43) [17], and hypoxia inducible factor-1α (HIF-1α) [18]. Other overexpressed genes, such as wild-type p53 inducible phosphatase-1 (WIP-1) [19] and lipocalin 2 (Lcn2) [20], could decrease MSC senescence during the process.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic manipulation promotes the viability of stem cell engraftment by overexpression of cytoprotective genes. The common overexpressed genes in promoting the survival of mesenchymal stem cells (MSCs) include v-Akt Murine Thymoma Viral Oncogene (AKT) [10], B-cell lymphoma 2 (Bcl-2) [11], heat shock protein 20 (Hsp20) [12], nuclear factor related (erythroid-derived 2)-like 2 (Nrf2) [13], heme oxygenase-1 (HO) [14,15], endothelial nitric oxide synthase (eNOS) [16], connexin 43 (Cx43) [17], and hypoxia inducible factor-1α (HIF-1α) [18]. Other overexpressed genes, such as wild-type p53 inducible phosphatase-1 (WIP-1) [19] and lipocalin 2 (Lcn2) [20], could decrease MSC senescence during the process.…”
Section: Introductionmentioning
confidence: 99%
“…The MSCs-HIF-1α are resistant against hypoxic, oxidative, and serumdeprived stress conditions (Kiani et al 2014).…”
Section: Genetic Manipulationmentioning
confidence: 99%
“…This study therefore suggested that the HSC niche microenvironment requires Hif‐2α to sustain normal hematopoiesis although the contribution of Hif‐2α deficiency in other tissues (i.e., tissues outside the BM) of Hif‐2α‐null recipient mice to the observed phenotype cannot be excluded. These genetic data, together with the observations that Hif‐1α and Hif‐2α regulate functions of endothelial cells , mesenchymal stem cells , and osteoblasts , all of which constitute HSC niches, imply that Hif‐dependent hypoxia signaling plays important roles in the BM microenvironment. Conditional deletion of Hif‐1α and Hif‐2α in functionally distinct niches, as it has been recently performed for other essential niche factors , will be the key to the understanding of Hif signaling in different HSC niches and its impact on HSCs and primitive progenitor cells.…”
Section: Hif Signaling In the Hsc Microenvironmentmentioning
confidence: 89%